Measuring jurors’ views on sentencing: results from the second Australian jury sentencing study - Warner, Kate Eleonore (Punishment & society, 2017)
This paper presents the results of the Victorian Jury Sentencing Study which aimed to measure jurors’ views on sentencing. The study asked jurors who had returned a guilty verdict to propose a sentence for the offender, to comment on the sentence given by the judge in their case and to give their opinions on general sentencing levels for different offence types. A total of 987 jurors from 124 criminal trials in the County Court of Victoria participated in this mixed-method and multi-phased study in 2013-2015. The results are based on juror responses to the Stage One and Stage Two surveys and show that the views of judges and jurors are much more closely aligned than mass public opinion surveys would suggest.